Bicycle Infrastructure Safety Assessment From the Perspective of Urban Development Specialists and Engineers - Miglė Zabielaitė-Skirmantė; Marija Burinskienė (The Baltic Journal of Road and Bridge Engineering)
The safety of bicycle infrastructure is a primary factor influencing bicycle travel. While cyclists’ perspectives on infrastructure safety are extensively studied, they are merely the end users. Decisions on infrastructure design are made by engineers and urban development specialists. Therefore, it is crucial to determine if these professionals’ safety assessments align with those of cyclists. A qualitative survey was conducted with 5 expert engineers and 5 urban development specialists, each having 5 to 20 years of experience in transportation infrastructure planning. Kendall’s coefficient of concordance W was used to assess the compatibility of their opinions. The results showed significant compatibility: W = 0.697 for engineers and W = 0.511 for urban development specialists. Seventeen cycling infrastructure installation schemes were evaluated. Both engineers (M = 10.0, SD = 0.0) and urban development specialists (M = 9.8, SD = 0.44) indicated the DT_2 option as providing the greatest sense of security, where the bicycle path is physically separated from both the carriageway and pedestrian path. The key findings reveal agreement on the safety of straight-street segments of bicycle infrastructure but diverging opinions at intersections zones. Urban development specialists are influenced by existing practices and legal frameworks lacking detailed cycling infrastructure guidelines at intersections. Engineers align more closely with cyclists’ perceptions, emphasising physical separation and speed reduction measures. The study concludes that urban development specialists need to better understand cyclists’ needs and prioritize safer infrastructure solutions.